2020
DOI: 10.3390/microorganisms8020251
|View full text |Cite
|
Sign up to set email alerts
|

The Helicobacter pylori HspR-Modulator CbpA Is a Multifunctional Heat-Shock Protein

Abstract: The medically important human pathogen Helicobacter pylori relies on a collection of highly conserved heat-shock and chaperone proteins to preserve the integrity of cellular polypeptides and to control their homeostasis in response to external stress and changing environmental conditions. Among this set of chaperones, the CbpA protein has been shown to play a regulatory role in heat-shock gene regulation by directly interacting with the master stress-responsive repressor HspR. Apart from this regulatory role, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Moreover, it has been recently demonstrated that H. pylori CbpA is a multifunctional protein, able to stimulate the ATPase activity of the major chaperone DnaK and to bind DNA. In addition, this DNA-binding activity can be modulated upon the direct interaction with the heat-shock master repressor HspR, suggesting the existence of reciprocal crosstalk between these two proteins [105].…”
Section: Hspr and Hrca Repressorsmentioning
confidence: 99%
“…Moreover, it has been recently demonstrated that H. pylori CbpA is a multifunctional protein, able to stimulate the ATPase activity of the major chaperone DnaK and to bind DNA. In addition, this DNA-binding activity can be modulated upon the direct interaction with the heat-shock master repressor HspR, suggesting the existence of reciprocal crosstalk between these two proteins [105].…”
Section: Hspr and Hrca Repressorsmentioning
confidence: 99%
“…Irrigation and weekly treatments were then resumed until week 8 when observations of visual quality were evaluated. In addition to encoding for genes involved in ROS defense protection, the genome of MBSA-MJ1 also encodes for multiple universal stress proteins that confer resistance to oxidative stress (uspABCEG), multiple heat shock proteins (grpE, htpX, hspQ, and hslR), and chaperone proteins (dnaJ, dnaK, groES/EL, clpB, cbpM, and cbpA; Supplementary Table S4; Kornitzer et al, 1991;Squires et al, 1991;Gragerov et al, 1992;Korber et al, 2000;Chae et al, 2004;Shimuta et al, 2004;Nachin et al, 2005;Pepe et al, 2020).…”
Section: Identification Of Genes Putatively Involved In Oxidative Defense Responsementioning
confidence: 99%